Alpha-synuclein pathology does not predict extrapyramidal symptoms or dementia - Parkkinen, L; Kauppinen, T; Pirttilä, T; Autere, J; Alafuzoff, I; Parkkinen, L (Wiley, 2004)
Intracytoplasmic aggregation of α-synuclein protein as Lewy bodies in the brainstem neurons is diagnostic for Parkinson's disease, whereas if this process also occurs in the cortical neurons, it is considered pathognomonic for dementia with Lewy bodies. However, the link between α-synuclein incorporation into inclusions, neuronal dysfunction, and clinical symptoms needs to be clarified. Another important issue of the pathogenetic puzzle is to understand where α-synuclein pathology begins and how it progresses in the brain. To study this, we collected all cases from autopsy material (N = 904) that had α-synuclein pathology in the dorsal motor nucleus of vagus, substantia nigra, and/or basal forebrain nuclei. In this way, our study has a unique design because the selection of material is entirely based on the presence of α-synuclein pathology regardless of clinical phenotype. Retrospective clinical assessment then showed that only 32 (30%) of 106 α-synuclein–positive cases were diagnosed with a neurodegenerative disorder. The distribution or load of α-synuclein pathology did not permit a dependable postmortem diagnosis of extrapyramidal symptoms or cognitive impairment. Some neurologically unimpaired cases had a reasonable burden of α-synuclein pathology in both brainstem and cortical areas, suggesting that α-synuclein–positive structures are not definite markers of neuronal dysfunction.